Musical taste and ingroup favouritism - Lonsdale, A.; North, Adrian (Sage Publications Ltd., 2009)
Musical taste is thought to function as a social ‘badge’ of group membership, contributingto an individual’s sense of social identity. Following from this, social identity theory predictsthat individuals should perceive and behave more favourably towards those perceived to sharetheir musical taste than towards those who do not. The fi ndings of two studies supported thesepredictions. The fi rst showed that stereotypes of the fans of different musical styles demonstrateingroup favouritism, and the second study used the minimal group paradigm to show thatindividuals allocate greater rewards to those believed to share their musical taste. This suggeststhat those who share our musical taste are likely to be considered ingroup members, and shouldbe subject to ingroup favouritism.